Socio-Psychological Characteristics of the Suspect’s Personal Profile During a Polygraphical Examination - Kovalchuk, Zoriana (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2022)
The article analyzes the expediency and importance of describing the personal profile of individuals during a polygraph survey and ascertaining their involvement in the commission of a crime. Since the field study on the involvement of individuals does not always can give a reliable conclusion, there is a need to create a psychological profile of the individual. A thorough analysis of personal characteristics that are dominant in the profile, a combination of reactions obtained through polygraph examinations and fixed nonverbal manifestations of a person during a polygraph examination, make it possible to conclude that the suspects are involved in the commission of a crime. Only in this case analysis of suspects’ profiles can make the most accurate and true conclusion. The results of the conducted research prove that it should be noted that the persons involved in the commission of the crime and persons not involved, the highest figure on the scale of "Reactive aggression". Unrelated to the crime, in contrast to those involved, there is a high rate on the "Irritability" scale, which indicates the presence of emotional instability and the tendency to react to the affective response in order to avoid tension. High rates on the scale of "Emotional lability" are revealed in both groups, but somewhat predominate in persons involved in a crime. It is worth noting that the persons involved in a crime, unlike those who are not involved, are more constrained, uncertain in themselves, rarely show caution in establishing contacts with others, but they seek to expand them. Persons not involved in committing a crime are dominated by respiratory failure, abnormal functioning of the gastrointestinal tract, and sleep problems. They have complicated functioning of attention. There is a feeling of anxiety, which is accompanied by various emotional reactions - shame, anger, guilt, fear.